Methodical basis of formation of digital space performance of contractual construction works - Bondar, O.A.; Medyanyk, V.Yu; Pokolenko, V.O.; Bushuyeva, N.S.; Mudra, M.S. (Ways to Improve Construction Efficiency, 2021)
A system of adaptive methodology is proposed, which is formed with the help of applied tools of construction organization and targeted organizational-technological and administrative development for the implementation of large-scale construction projects through the format of a special development company. On the basis of step-by-step modeling, scenario-simulation and stochastic adjustment, subsequent multicriteria evaluation (according to 4 criteria) of the toolkit subsystem, the final index-priority of one alternative to the MBDP cycle organization is determined in relation to another. and KFOR) on technological, functional and cost characteristics of the MBDP cycle, in which the organization of construction is the most complex in terms of functional and technical content, and the preparatory phase (including the formation of an effective administrative structure) is most responsible for the targeted use of resources for project product formation, with preset parameters. The results of the study were transformed into a system of application software modules "BIM-modules of construction organization for MBDP". This set of programs (as a result of its implementation in construction practice) creates a scientific and applied means of training, organizational and technological, content-functional and administrative support of the MBDP cycle corresponding to modern needs of the construction market and the system of construction development. The scientific and theoretical value of the study is that for the first time from the standpoint of modern realities of the construction market of Ukraine and the requirements of development in housing construction, developed a methodology for construction as part of a single cycle of administration managed by a temporary enterprise-special development company. A fundamental change in the tools of construction organization has been implemented, in which the advantages of organizational and technological models of updated type and content are combined with the capabilities of BIM-technologies, structural reengineering, which ultimately provides reliable preventive (before or at the beginning of the project implementation cycle) structural decisions on the basis of stage-by-stage, multicriteria examination of decisions, with possible detection of influence of these decisions on final results of the project both for the customer, the developer, and for the organizations-executors.